Implementasi Penghayatan Nilai-Nilai Pancasila Terhadap Keberagaman Sebagai Upaya Penguatan Identitas Manusia Indonesia - Anisa Nurul Jannah; Iksan, Bagas; Elfia, Delisa; Arissah, Euis; Aulia Damayanti Marpaung, Femmy; Fitri Yanti, Eva (Jurnal Gentala Pendidikan Dasar, 2024)
Pancasila is a guideline in state life, namely as a basis, ideology, outlook on life, soul of the nation, national personality, ideals and goals of the nation, and the philosophy of life of the Indonesian nation. Diversity provides reinforcement in achieving the ideals of the nation, and supports the implementation of an independent curriculum to realize students who apply the values of Pancasila. The purpose of this study is to describe the implementation of Pancasila values towards diversity as an effort to strengthen Indonesian human identity. The research method used is a qualitative descriptive method with the aim of obtaining detailed information about the appreciation and implementation of Pancasila values. Data collection techniques are observation, interviews, and documentation. The result of this study is the Implementation of Appreciation of Pancasila Values for Diversity has been carried out at SDN 15/IV Jambi as an effort to strengthen Indonesian human identity